In vitro mechanical and corrosion properties of biodegradable Mg–Ag alloys. Issue 6 (18th January 2013) - Tie, D.; Feyerabend, F.; Hort, N.; Hoeche, D.; Kainer, K. U.; Willumeit, R.; Mueller, W. D.
<x xml:space="preserve">Abstract</x> Binary magnesium–silver (Mg–Ag) alloys were designed as antibacterial material to treat infections in an implant site. The mechanical and electrochemical measurements were performed on three casting Mg–Ag alloys under cell culture conditions. The composition and distribution of the corrosion layer was analyzed by microscopy and X‐ray photoelectron spectroscopy. In cell culture media, Mg–Ag alloys show higher, but still acceptable general corrosion rates while less susceptibility to pitting corrosion than pure Mg with increasing content of silver. This study indicates that Mg–Ag alloys have satisfactory corrosion properties and much better mechanical properties than pure magnesium as a functional biodegradable material.